Managing technological development: lessons from the newly industrializing countries - Dahlman, Carl J.; Ross-Larson, Bruce Clifford; Westphal, Larry E. (Washington, D.C., U.S.A.: World Bank, 1985)
This paper draws on the experience of developing countries to summarize some general lessons about what is important in managing their technological development. First, the paper describes the technological development of an archetypical successful firm, and that description to introduce basic concepts. Second, there's a description of the steps firms must take in choosing technology. Third, how firms and countries augment their technological capability is described. Fourth, the paper also describes what is involved in combining foreign and domestic technological elements- that is, in combining foreign and domestic information, means, and understanding.
Includes bibliographical references: p. 55.
ne 10/04/2018
Loans
Keywords: Technological innovations; Technology; Industrial productivity